2020
DOI: 10.1088/1755-1315/421/6/062010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the process of pelleting for pre-sowing treatment of flax seeds

Abstract: The paper presents a computational method that allows to predict the process of drainage of flax seeds with expanded perlite and biohumus for complex pre-sowing treatment with preliminary irradiation of seeds in the infrared range. From a methodological point of view, in the process of seed granulation, the efficiency depends on the adhesive bond arising in the process of rolling and dispersing. To solve this problem, the calculations of mathematical models of the process of granulation of seeds and the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the movement of the material along the x axis will be neglected by u ≈ 0. With regard to the problem under study on a symmetric integration interval, in the case of a limited solution at both ends of the segment [-t, +t], we have [4][5][6][7][8][9][10][11][12][13][14][15]:…”
Section: Development Of a Mathematical Modelmentioning
confidence: 99%
“…Substituting the functions of contact normal stresses (5) with empirical coefficients in (9), we obtain the values of the angle of the optimal position of the blade: for the inner contour β = 13º,5΄; for the middle section -β = 10º,9΄; for an external contour -β = 7º,2΄.…”
Section: Optimization Of the Blade Positionmentioning
confidence: 99%
“…In the strategic policy of the development of food and processing industries of the Russian Federation, the priority direction is the introduction and use of energy-efficient, environmentally friendly, integrated, waste-free technologies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%